2009
DOI: 10.1007/s00439-009-0692-z
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of atopic dermatitis to chromosomes 4q22, 3p24 and 3q21

Abstract: Atopic dermatitis (AD) is a common, itchy skin disease of complex inheritance characterized by dermal and epidermal inflammation. The heritability is considerable and well documented. To date, four genome scans have examined the AD phenotype, showing replicated linkage at 3p26-22, 3q13-21 and 18q11-21. Our previous AD scan showed evidence of linkage to loci at 3p and 18q, and furthermore at 4p15-14. In order to further investigate the genetic basis of AD, we collected and analysed a new Danish family sample co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
0
14
0
2
Order By: Relevance
“…Follow-up fine-mapping of eight markers in the 11p14 locus suggested a pleiotropic effect for the three allergic diseases, AD, asthma and allergic rhinitis. More recently, the Danish team followed up on their previous evidence for linkage at the 3p, 4q and 18q loci, in addition to previous evidence for linkage at 3q, in an independent sample of 130 AD sib-pair families, and concluded the strongest evidence for linkage was to 3p34, 3q21, and 4q2221. From these follow-ups, however, conclusions are speculative at best, given that each of the regions where significant evidence of linkage has been identified contains multiple candidate genes.…”
Section: Discovery Of Atopic Dermatitis Genes Using Traditional Appromentioning
confidence: 99%
“…Follow-up fine-mapping of eight markers in the 11p14 locus suggested a pleiotropic effect for the three allergic diseases, AD, asthma and allergic rhinitis. More recently, the Danish team followed up on their previous evidence for linkage at the 3p, 4q and 18q loci, in addition to previous evidence for linkage at 3q, in an independent sample of 130 AD sib-pair families, and concluded the strongest evidence for linkage was to 3p34, 3q21, and 4q2221. From these follow-ups, however, conclusions are speculative at best, given that each of the regions where significant evidence of linkage has been identified contains multiple candidate genes.…”
Section: Discovery Of Atopic Dermatitis Genes Using Traditional Appromentioning
confidence: 99%
“…45 Runx3 resides on human chromosome 1p36.1, 46 which maps to a region containing susceptibility genes for asthma, 47 and on mouse chromosome 4, 48 which contains a susceptibility gene for atopic dermatitis. 49 Loss of Runx3 results in spontaneous development of inflammatory bowel disease, 14 as well as constitutive airway hyperreactivity and eosinophilic inflammation. 43 We demonstrated that Runx3 (but not Runx1 or Runx2 ) expression was downregulated in the jejunums of sensitized and challenged WT and Runx3 +/− mice and that the increases in Pim1 kinase mRNA and protein levels were greater in the jejunums of peanut-sensitized and challenged Runx3 +/− mice than in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…(34) Genome-wide linkage analysis had been used in different populations to date, and multiple candidate regions on multiple chromosomes had been associated with AD. (35)(36)(37)(38)(39) The linkage regions vary in different populations, and there is no extensive overlap among studies. Some candidate regions are close to functional genes linked to the various phenotypes of AD.…”
Section: Molecular Genetic Tools Of Atopic Dermatitismentioning
confidence: 99%
“…Systemic, well-powered, genome-wide surveys using GWAS and immunochip analyses have estimated the relationship between SNP and susceptibility to AD. (31,39,40) It is well established that common loss of function variants of FLG are a major predisposing factor for AD. As for example, the FLG mutations are involved in AD and are featured in some review articles.…”
Section: Molecular Genetic Tools Of Atopic Dermatitismentioning
confidence: 99%